2010
DOI: 10.1118/1.3284976
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomatic vessel wall detection and quantification of wall thickness in computed tomography images of human abdominal aortic aneurysms

Abstract: While further refinement is needed to fully automate the outer wall segmentation algorithm, these preliminary results demonstrate the method's adequate reproducibility and low interobserver variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
0
73
0
1
Order By: Relevance
“…The mean diameter was 52.36 mm with a standard deviation 1.49 mm, average pixel size of 0.7781 mm, and the mode value of slice spacing 3.0 mm. CT images between the renal arteries and approximately 3 inches distal to the iliac bifurcation were segmented using our in-house MATLAB code VESSEG [15], shown schematically in Fig. 1.…”
Section: Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean diameter was 52.36 mm with a standard deviation 1.49 mm, average pixel size of 0.7781 mm, and the mode value of slice spacing 3.0 mm. CT images between the renal arteries and approximately 3 inches distal to the iliac bifurcation were segmented using our in-house MATLAB code VESSEG [15], shown schematically in Fig. 1.…”
Section: Image Segmentationmentioning
confidence: 99%
“…To that end, Martufi et al [14] reported the validation of a set of MATLAB routines for estimating regional vessel wall thickness from CT images by comparing it with postmortem AAA tissue measurements [11], resulting in an average relative difference of 7.8%. A framework for semiautomatic vessel wall detection and quantification of thickness using contrastenhanced CT images was described by Shum et al [15], resulting in low repeatability and reproducibility errors when compared to the manual segmentations performed by trained vascular surgeons. Quantitative assessment of AAA geometry [16] has shown promising results, with wall thickness being one of the morphological indicators significant for rupture risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the AAA wall is nonuniform [49][50][51], influenced by many factors [52], and may [53] or may not [54] change between ruptured and [17], indicating regions at higher risk of rupture, while thin-walled areas could be exposed to high wall stress and be at high risk for rupture. Biomechanical AAA studies report different average population thicknesses (see Table 2, which may be explained by fundamentally different measurement methods and the difficulty specifying the outer border of the adventitia.…”
Section: Aaa Wall Thicknessmentioning
confidence: 99%
“…The authors notice, however, that the result obtained need to be checked against image collections coming from different CT scanners and recorded with different layer thicknesses. When analysing other articles regarding aorta segmentation, it can be seen that attempts to segment automatically, described earlier, were abandoned in favour of semi-automatic segmentation with operator input ( [5,6]). An exhaustive presentation of various approaches to the segmentation of the abdominal aorta can be found in [14].…”
Section: When Analysing Work By Researchers From Universitymentioning
confidence: 99%